Electrocatalytic Reduction of CO2 to Value‐Added Chemicals via C–C/N Coupling - Liu, Junling; Zhang, Xuejing; Yang, Rui; Yang, Yongan; Wang, Xi (Advanced energy and sustainability research, 2023)
The efficient conversion and utilization of CO2 is imminent due to the increase of global CO2 emissions year by year, so the strategy of electrocatalytic CO2 reduction to high value‐added chemicals comes into being. The CO2 reduction reaction (CO2RR) can yield diversified products, including C1 (like CO, CH4, etc.), C2 (like C2H4, C2H5OH, etc.), and other multicarbon compounds. Thereinto, selective transformation to C2 compounds is relatively significative by reason of high industrial value but being greatly challenging, particularly involving complex CC coupling. Herein, the reaction mechanisms of several C2 products (including C2H4, C2H5OH, and H2C2O4) and corresponding latest research progress are summarized and discussed. Besides, N atoms, from N2, nitrates, and nitrites, are integrated into CO2RR to yield nitrogen‐containing organics (like urea, amides, and amines), broadening the application field of CO2RR. Therefore, the part on the electrocatalytic coupling of CO2 and nitrogen sources (including N2, NO3−, NO2−) by CN bonds is also delved in this review, including recent advances, reaction mechanisms, and related key intermediates. Herein, the latest significant attempts on CC/N coupling (converting CO2 and N‐contained compounds to useful organics) as well as the reaction mechanisms are highlighted for providing an advanced perspective toward high‐value conversion of CO2. Besides, this review discusses that the emerging fields remain critically challengeable for further optimizing relevant processes in performance, mechanisms, and commercialization.